2013
DOI: 10.3190/jgeosci.142
|View full text |Cite
|
Sign up to set email alerts
|

Chrysoberyl-sillimanite association from the Roncadeira pegmatite, Borborema Province, Brazil: implications for gemstone exploration

Abstract: The first occurrence of chrysoberyl in the Borborema Pegmatite Province (BPP) in northeastern Brazil is reported from up to 0.5 m large boulders in the dumps covering the Roncadeira pegmatite, worked in the 1940's for Sn-and Ta-ore concentrate. The chrysoberyl occurs in tabular, transparent light yellow crystals, up to two centimeters across. It is associated with quartz and fibrolitic sillimanite along centimeter-thick sigmoidal shear zones crosscutting banded sodic aplite facies of the pegmatite. Along the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Magmatic chrysoberyl in assemblage with beryl, sillimanite and gahnite was described from the highly-evolved, peraluminous Belvís de Monroy leucogranite, Spain (Merino et al , 2013). However, most occurrences of chrysoberyl consider it to have formed from the breakdown of primary beryl as a result of metamorphic overprinting of the pegmatite e.g: Kolsva, Sweden; Haddam, USA; and Maršíkov, Czech Republic (Franz and Morteani, 1984, 2002; Černý et al , 1992); Kalanga Hill, Zambia (Žáček and Vrána, 2002); Ethel Mary and Virorco, Argentina (Lira and Sfragulla, 2011; Galliski et al , 2012); New York, USA (Lupulescu et al , 2012); Roncadeira, Brazil (Beurlen et al , 2013); and Mt. Begbie, Canada (Dixon et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Magmatic chrysoberyl in assemblage with beryl, sillimanite and gahnite was described from the highly-evolved, peraluminous Belvís de Monroy leucogranite, Spain (Merino et al , 2013). However, most occurrences of chrysoberyl consider it to have formed from the breakdown of primary beryl as a result of metamorphic overprinting of the pegmatite e.g: Kolsva, Sweden; Haddam, USA; and Maršíkov, Czech Republic (Franz and Morteani, 1984, 2002; Černý et al , 1992); Kalanga Hill, Zambia (Žáček and Vrána, 2002); Ethel Mary and Virorco, Argentina (Lira and Sfragulla, 2011; Galliski et al , 2012); New York, USA (Lupulescu et al , 2012); Roncadeira, Brazil (Beurlen et al , 2013); and Mt. Begbie, Canada (Dixon et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This paragenesis was complemented by Beurlen et al (2010Beurlen et al ( , 2013 with the description of chrysoberyl in this pegmatite (the first one in the BPP) in association with sillimanite and presence of "zinconigerite-6N6S" a variety of the nigerite group. Most of the pegmatite lenses of the Roncadeira-Corredor group today are almost completely covered by regolith, waste and soil.…”
Section: Local Geologymentioning
confidence: 84%
“…Fibrous sillimanite, quartz and porhyroblastic chrysoberyl found only in reddish intensively sheared parts of the sample (Figs. 5 and 6) were discussed in detail by Beurlen et al (2013) and allowed to establish the temperature and pressure of its formation at approximately 600 ° C and 3.5 to 5.0 kb. Preliminary EPMA (Electron Probe Micro Analyses) data in that study indicated a Zn-dominant composition of the nigerite group grains, without a detailed description.…”
Section: Pretrographymentioning
confidence: 99%
“…9d). An origin of chrysoberyl by metamorphic overprint has also been documented in several beryl-bearing granitic pegmatites Morteani, 1984, 2002;Černý et al, 1992;Beurlen, et al, 2013). The possible reaction describing the formation of metamorphic chrysoberyl could be written as: Be 3 Al 2 Si 6 O 18 (beryl) + 4(K, Na)AlSi 3 O 8 (feldspar) + 4H + 3BeAl 2 O 4 (chrysoberyl) + 18SiO 2 (quartz)…”
Section: Metamorphic Overprint Of Pegmatitesmentioning
confidence: 88%